2019
DOI: 10.1016/j.jvs.2018.04.056
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of upper extremity interventions for chronic critical ischemia

Abstract: Upper extremity interventions for critical ischemia are associated with a high rate of success. Major amputations are rare and the many can be treated nonoperatively. In appropriately selected patients, both endovascular and open interventions have a high rate of success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…In the Cheun et al study, the status of the palmar arch prior to intervention was also predictive of wound healing, clinical success, cumulative patency, and freedom from MALE. 13 PTA of BTE vessels is safe. Two studies reported no complications, and the remaining studies reported predominately minor complications pertaining to access site hematoma or pseudoaneurysm.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the Cheun et al study, the status of the palmar arch prior to intervention was also predictive of wound healing, clinical success, cumulative patency, and freedom from MALE. 13 PTA of BTE vessels is safe. Two studies reported no complications, and the remaining studies reported predominately minor complications pertaining to access site hematoma or pseudoaneurysm.…”
Section: Discussionmentioning
confidence: 91%
“…Cheun et al examined the outcomes of patients presenting with CHI due to BTE obstructive disease who underwent non-operative versus operative management (endovascular or surgical bypass). 13 Of 108 patients (average age = 59; 56% male), 34 underwent endovascular therapy with a median 1.5 vessels (UA, RA and/or IA) treated, 21 underwent a saphenous vein bypass to either the RA (12) and/or ulnar artery (11), and 53 were managed conservatively. At baseline, there was a higher proportion of patients with diabetes in the endovascular and surgical bypass groups compared with the no intervention group (94% and 81% vs 72%, p = 0.03).…”
Section: Conservative Management Endovascular Management or Surgical Bypassmentioning
confidence: 99%
“…For this reason, many patients do not undergo active management but only observation. To the best our knowledge, the only recent large series on outcomes of bypass surgery using the saphenous vein in below-the-elbow arterial atherosclerotic occlusive disease was reported by Cheun et al [22]. In their report, open intervention (bypass surgery) and endovascular intervention showed a high success rate and the incidence of major amputation was decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Conservative therapy can be applied to patients with significant comorbidities or minimal symptoms. Cheun et al [ 6 ] reported the results of conservative therapy in 53 (49%) patients among the 108 patients with symptomatic below-the-elbow atherosclerotic disease. The 3-month symptom relief rate was 31%, and the wound healing rate was 69%.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, no major amputation was performed in 30 days, which might be related to the abundant collateral circulation in the UE. However, conservative therapy in patients with no revascularization options resulted in lower wound healing and symptom relief rates than endovascular and bypass interventions [ 6 ]. Endovascular treatment for UE arterial occlusive disease is not popular because of the relative infrequency of interventions or the underlying causes of arterial disease.…”
Section: Discussionmentioning
confidence: 99%